MARK NOLL AND GLOBAL FAITH. - Jenkins, Philip (Fides et historia, 2016)
The article talks about the work of American historian Mark Noll on the topic of global Christianity. Topics discussed include the author's assertion of Christianity being a global religion, and Mark Noll's contributions to the topic that the books "The New Shape of World Christianity: How American Experience Reflects Global Faith" and "Clouds of Witnesses: Christian Voices from Africa and Asia" among others.